Astrologi Hindu dalam Dinamika Budaya Pertanian Subak: Studi Etnografi di Kabupaten Tabanan - Wartayasa, I Ketut (Jurnal Penelitian Agama Hindu, 2025)
The Subak agricultural system in Bali functions not only as a traditional irrigation structure but also as an integration of ecological knowledge and Hindu spirituality, particularly through the use of the Wariga astrological system. In the context of modernization and social transformation, this astrological practice is increasingly challenged, raising concerns over the sustainability of local cultural knowledge. This study aims to explore the role and transformation of Hindu astrology in the agricultural culture of Subak communities in Tabanan Regency, as well as to examine community-driven efforts to revitalize such traditional knowledge. Using an ethnographic approach, data were collected through participant observation, in-depth interviews, document analysis, and focus group discussions with local farmers and customary leaders. The findings reveal that Wariga remains a significant epistemological framework for determining planting schedules and agricultural rituals, despite the ongoing hybridization with modern calendrical systems. Adaptation strategies such as the digitalization of Balinese calendars, the involvement of customary institutions, and cultural education initiatives have become essential in maintaining the relevance of Wariga. This research highlights the importance of recognizing local epistemologies in sustainable development and the need to integrate spirituality, traditional knowledge, and agricultural policy. This research confirms the importance of integrating local epistemologies in sustainable agricultural policy, while enriching non-Western scientific discourse.